Práticas Educativas Comparadas em Educação do Campo e os Desafios da Formação Omnilateral na América Latina - Villela, Fabio Fernandes [UNESP] (My University, 2011)
This text aims to present the challenges and opportunities of omnilateral formation in Latin America as elaborated in Villela (2009-2010). This work has the horizon systematize the educational practices of the "Third World ", i.e. originating from the educational experience of Latin America, Africa and Asia. In the struggle for emancipation, these countries have built and are building unique educational practices. In this sense, we start questioning the historical and theoretical topic, omnilateral formation, and deployment, we discuss the Latin American school and omnilateral formation. We question specifically issues relating to “intellectuals and the organization of culture” in "schools in the countryside" in Cuba (1960- 1975). The issue of "intellectuals and the organization of culture", in a gramscian perspective (GRAMSCI, 2000), was addressed in several works throughout our academic career (VILLELA, 2003; 2008; 2009-2010). In order to further these issues, we address the challenges of formation for children and youth of the field in Latin America. By analyzing the educational practices in the schools in the countryside, emerges the theme of contemporary global justice.

Este texto tem por objetivo apresentar os desafios e as possibilidades da formação omnilateral na América Latina conforme elaborado em Villela (2009-2010). Este trabalho tem por horizonte sistematizar as práticas educativas do “Terceiro Mundo”, isto é, originadas da experiência educacional dos países da América Latina, África e Ásia. No processo de luta pela emancipação, esses países construíram e estão construindo práticas educativas originais. Nesse sentido, partimos da problematização histórico-teórico do tema, formação omnilateral, e por desdobramento, abordamos a América Latina, escola e formação omnilateral. Problematizamos especificamente as questões relativas aos intelectuais e a organização do trabalho pedagógico nas “escolas no campo” em Cuba (1960-1975). A questão dos “intelectuais e a organização da cultura”, sob uma perspectiva gramsciana (GRAMSCI, 2000), foi abordada em diversos trabalhos ao longo de nossa trajetória acadêmica (VILLELA, 2003; 2008; 2009-2010). No sentido de aprofundar tais questões, abordamos os desafios da formação de crianças e jovens do campo na América Latina. Ao analisarmos as práticas educativas em educação do campo, emerge a temática contemporânea da justiça global.

Este texto tiene como objetivo presentar los retos y posibilidades de formación omnilateral en América Latina como se detalla en Villela (2009-2010). Este trabajo tiene como horizonte sistematizar las prácticas educativas del "Tercer Mundo", es decir, se originó de la experiencia educativa en América Latina, África y Asia. En la lucha por la emancipación, estos países se han construido y están construyendo prácticas educativas únicas. En consecuencia, comenzó con la problematización histórico-teórica del tema, la formación omnilateral y despliegue, se discute América Latina, la escuela y la formación omnilateral. A continuación, se discute la cuestiones específicamente relacionadas con los intelectuales e la organización del trabajo pedagógico en las "escuelas en el campo" en Cuba (1960-1975). El tema de los "intelectuales e la organización de la cultura " bajo una perspectiva gramsciana (GRAMSCI, 2000), se abordó en varios trabajos a lo largo de nuestra carrera académica (VILLELA, 2003; 2008; 2009-2010). Con el fin de avanzar en estos temas, se abordan los retos de la educación de los niños y jóvenes del campo en América Latina. Mediante el análisis de las prácticas educativas de la educación en el campo, surge el tema de la justicia global contemporánea.
Las prácticas educativas comparadas en educación en el campo y los desafíos de la formación omnilateral en América Latina
Educational practices compared in rural education and the challenges of omnilateral formation in Latin America
Keywords: práticas educativas; educação do campo; formação omnilateral; América Latina; justiça global; educational practices; rural education; omnilateral formation; Latin America; global justice